The Students’ Perception of Apprehending, Synthesizing, Analyzing, and Responding (ASAR) Speaking Process-Based Instructional Materials - Syaripuddin, Rahmatullah (English Education: Jurnal Tadris Bahasa Inggris, 2022)
This study was based on the students’ problems regarding English teaching, especially English materials of speaking skills. The students have poor English speaking ability because the lecturer did not have instructional materials related to their department. The media and method was not attractive and the instructional facilities were not enough to facilitate a good learning process. The objective of the research was to develop Englishspeaking materials by integrating Apprehending, Synthesizing, Analyzing, and Responding (ASAR) based material. The sample of the study was Biological students of Muhammadiyah University of Parepare, Indonesia. The method used in this research was developmental research which attempts to develop English-speaking materials based on the modified ADDIE approach (Analyze, Design, and Development). The result of the study was an authentic English-speaking materials for Biological students of Muhammadiyah University of Parepare. The instructional materials focused on input, process, and output. After the materials were given the student’s perception changed into very good value. It means that English-speaking instructions for the Biology department have good quality in the form of course map, lesson plan, lecturer's manual, topic, video clips, materials, students' worksheets, learning activities, and assessment.